Staphylococcus aureus toxin gene hitchhikes on a transferable antibiotic resistance element - Otto, Michael (Landes Bioscience, 2010)
Virulence and antibiotic resistance of the dangerous human pathogen Staphylococcus aureus are to large extent determined by the acquisition of mobile genetic elements (MGEs). Up to now, these elements were known to comprise either resistance or virulence determinants, but not a mixture of the two. Queck et al. now found a cytolysin gene of the phenol-soluble modulin (PSM) family within SCCmec elements, which contain methicillin resistance genes and are largely responsible for the spread of methicillin-resistant S. aureus (MRSA). The novel gene, called psm-mec, had a significant impact on virulence in MRSA strains that do not produce high levels of genome-encoded PSMs. This first example of a combination of toxin and resistance genes on one staphylococcal MGE shows that such bundling is possible and may lead to an even faster acquisition of toxin and resistance genes by S. aureus and other staphylococcal pathogens.